IMPROVING SPATIAL VISUAL ABILITIES IN CHILDREN AGED 4-5 YEARS USING THE THREE SAME THINGS GAME - Aprilia Pratiwi, Rizky (Asosiasi Prodi Manajemen Administrasi Pendidikan Indonesia (APMAPI), 2024)
This research aims to know the effect of using the three same things game on the visual-spatial intelligence of children aged 4-5 years. This research used a quantitative method with a pre-experimental type of research. This research used a one-group pretest-posttest design. The sample in this research consisted of 22 children aged 4-5 years. The sampling technique used was purposive sampling. The data collection techniques used in this research were observation and documentation. Observations were done using an observation sheet tested for validity, and all the valid indicators were declared. Then, they were tested for reliability using Cronbach's alpha formula and were declared very reliable with an X score of 0,939 and a Y score of 0,910. The results of the research show that the average N-Gain score is 0.48, which means that the influence of the three same things game on children's visual-spatial intelligence is in the medium category. Then, the test results using a simple linear regression test obtained a significance value of 0.000 less than 0.05 (0.000<0.05); this proves an influence between the three same things on the visual-spatial intelligence of children aged 4-5 years.